Analysis of the efficiency of geomechanical model of mine working based on computational and field studies - Fomychov, V; Mamaikin, O; Demchenko, Yu; Prykhorchuk, O; Jarosz, J (National Mining University, 2018)
Purpose is to substantiate the efficiency of geomechanical model of the mine working on the basis of qualitative and quantitative parameters of stress and strain state of the mine working and to compare the results of computational experiment both with the results obtained while designing mine working support and with the results of field studies under mine conditions. Methods. The studies consisted of three stages. Stage one involved development of the computational model and, using a finite-element method (ANSYS Software Package), and performance of computational experiment for mining and geological conditions of MM “Pokrovske”. Stage two involved field measurements in the mine working with the support pattern developed according to the results of first stage of the research. Characteristic points were selected to determined separate stress and deformation components of a geomechanical system. Stage three dealt with comparative analysis of both computational and field experiments to define the efficiency of the selected computational model and the engineering solutions. Findings. The substantiated physical and mathematical model as well as geometry of computational region of the geomechanical system have made is possible to determine to a high precision stress and strain state of all the components of mine working support and neighbouring rock mass. Analysis of changes in mine working border, while calculating and full-scale measuring, has demonstrated high accuracy degree in description of deformation processes within the rock mass. Qualitative changes in stresses within the selected anchors, in the process of the stope plane movement, correspond in their appearance to the curves of graphs obtained as a result of calculations. Originality. For the first time, complex multicriteria approach has been proposed and applied to determine efficiency of the selected support scheme based on the measurements of mine working border displacement and internal effects of the support components; the approach makes it possible to evaluate adequacy of the selected computational scheme while predicting changes in the geomechanical system state. Practical implications. The developed innovative methodology to prove the efficiency of selecting optimal system for mine working support helps reduce design costs and cut production expenses while mounting and operating the support from a holistic perspective. Validation of the fact that calculated results of stress and strain state of a geomechanical system correspond to the data of field measurements in terms of various stress and deformation criteria provides the possibility of the computational model interpolation with respect to the mine workings driven and designed under similar mining and geological conditions.

Мета. Обґрунтування ефективності геомеханічної моделі виїмкової виробки на основі порівняння якісних і кількісних параметрів напружено-деформованого стану виїмкової виробки за результатами розрахунку обчислювального експерименту з отриманими на етапі проектування кріплення виробки й натурними дослідженнями в шахтних умовах. Методика. Дослідження проводилися в три етапи. На першому етапі розроблялася розрахункова модель і за допомогою методу скінченних елементів (програмний пакет ANSYS) проводився обчислювальний експеримент для гірничо-геологічних умов шахтоуправління «Покровське». На другому етапі виконані натурні заміри у виробці зі схемою кріплення, визначеною за результатами першого етапу досліджень. Були обрані характерні точки, в яких визначалися окремі компоненти напружень або деформацій геомеханічної системи. Третій етап полягав у проведенні порівняльного аналізу даних обчислювального й натурного експерименту з метою визначення ефективності обраної розрахункової моделі й прийнятих технологічних рішень. Результати. Обґрунтовані фізико-математична модель та геометрія розрахункової області геомеханічної системи дозволили з високою точністю визначити напружено-деформований стан усіх елементів кріплення виробки й приконтурного породного масиву. Аналіз зміни контуру виробки при розрахунках і натурних вимірах показав високий ступінь точності описання деформаційних процесів, що протікають у породному масиві. Якісні зміни напружень в обраних анкерах при русі площини очисного вибою відповідають за видом кривим графіків, отриманих у результаті розрахунків. Наукова новизна. Вперше запропоновано та використано комплексний багатокритеріальний підхід для визначення ефективності обраної схеми кріплення, заснований на вимірах переміщень контуру виробки і внутрішніх зусиль елементів кріплення, що дозволяє оцінити адекватність обраної обчислювальної схеми при прогнозуванні зміни стану геомеханічної системи. Практична значимість. Розроблена нова методика підтвердження ефективності вибору оптимальної системи підтримання виїмкової виробки дозволяє комплексно скоротити затрати на проведення проектних заходів та зменшити витрати виробництва при установці й експлуатації кріплення. Підтвердження відповідності результатів розрахунків напружено-деформованого стану геомеханічної системи і даних натурних замірів за різними критеріями напружень та деформацій забезпечує можливість інтерполяції обчислювальної моделі для пройдених виробок і виробок, що проектуються, у схожих гірничо-геологічних умовах.

Цель. Обоснование эффективности геомеханической модели выемочной выработки на основании сравнения качественных и количественных параметров напряженно-деформированного состояния выемочной выработки по результатам расчета вычислительного эксперимента с полученными на этапе проектирования крепи выработки и натурными исследованиями в шахтных условиях. Методика. Исследования проводились в три этапа. На первом этапе разрабатывалась расчетная модель и при помощи метода конечных элементов (программный пакет ANSYS) проводился вычислительный эксперимент для горно-геологических условий шахтоуправления «Покровское». На втором этапе выполнены натурные замеры в выработке со схемой крепления, определенной по результатам первого этапа исследований. Были избраны характерные точки, в которых определялись отдельные компоненты напряжений или деформаций геомеханической системы. Третий этап заключался в проведении сравнительного анализа данных вычислительного и натурного эксперимента с целью определения эффективности выбранной расчетной модели и принятых технологических решений. Результаты. Обоснованные физико-математическая модель и геометрия расчетной области геомеханической системы позволили с высокой точностью определить напряженно-деформированное состояние всех элементов крепи выработки и приконтурного породного массива. Анализ изменения контура выработки при расчетах и натурных замерах показал высокую степень точности описания деформационных процессов, протекающих в породном массиве. Качественные изменения напряжений в выбранных анкерах при движении плоскости очистного забоя соответствуют по виду кривым графиков, полученных в результате расчетов. Научная новизна. Впервые предложен и использован комплексный многокритериальный подход для определения эффективности выбранной схемы крепления, основанный на замерах перемещений контура выработки и внутренних усилий элементов крепления, позволяющий оценить адекватность выбранной вычислительной схемы при прогнозировании изменения состояния геомеханической системы. Практическая значимость. Разработанная новая методика подтверждения эффективности выбора оптимальной системы поддержания выемочной выработки позволяет комплексно сократить затраты на проведение проектных мероприятий и уменьшить издержки производства при установке и эксплуатации крепи. Подтверждение соответствия результатов расчетов напряженно-деформированного состояния геомеханической системы и данных натурных замеров по различным критериям напряжений и деформаций обеспечивает возможность интерполяции вычислительной модели для пройденных и проектируемых выработок в схожих горно-геологических условиях.
Keywords: rock mass; stress and strain state; field experiments; anchors; mine working borders; mine working